ÉTUDE DES EFFETS NON LINÉAIRES SUR LES PROPRIÉTÉS DE TRANSPORT ÉLECTRONIQUES DANS LES SUPERRÉSEAUX AlXGa1-XAs - MEGHOUFEL Zahira Faiza (My University, 2013)
In this work, we study the effects of electron-electron interaction on electronic transport properties of a AlxGa1-xAs superlattice. This phenomenon induces a nonlinearity in the response system. The nonlinear Schrödinger equation is formulated in terms of the effective potential. The transfer matrix and the plane waves formalisms were applied to evaluate the electronic transmission and the type of states in the quantum structure. There is an appearance of a degeneracy state within the well, which, under an external field influence, splits into two. Both the two states evolve towards higher energies.
Keywords: Superlattice, Nonlinearity, Transfer-matrix, Degeneracy state.